Accelerating the genetic diagnosis of neurological disorders presenting with episodic apnoea in infancy. (July 2022) - Silksmith, Bryony; Munot, Pinki; Starling, Luke; Pujar, Suresh; Matthews, Emma
Summary: Unexplained episodic apnoea in infants (aged ≤1 year), including recurrent brief (<1 min) resolved unexplained events (known as BRUE), can be a diagnostic challenge. Recurrent unexplained apnoea might suggest a persistent, debilitating, and potentially fatal disorder. Genetic diseases are prevalent among this group, particularly in those who present with paroxysmal or episodic neurological symptoms. These disorders are individually rare and challenging for a general paediatrician to recognise, and there is often a delayed or even posthumous diagnosis (sometimes only made in retrospect when a second sibling becomes unwell). The disorders can be debilitating if untreated but pharmacotherapies are available for the vast majority. That any child should suffer from unnecessary morbidity or die from one of these disorders without a diagnosis or treatment having been offered is a tragedy; therefore, there is an urgent need to simplify and expedite the diagnostic journey. We propose an apnoea gene panel for hospital specialists caring for any infant who has recurrent apnoea without an obvious cause. This approach could remove the need to identify individual rare conditions, speed up diagnosis, and improve access to therapy, with the ultimate aim of reducing morbidity and mortality.